A DEA-SFA COMPARISON OF THE IMPACT OF ICT’S UTILIZATION - Fatulescu, Puiu (European Scientific Journal, ESJ, 2013)
This article has the purpose of comparing different statistical methods of measuring efficiency, data envelopment analysis and stochastic frontier analysis. An adjacent objective is to assess the impact of the information and communication technologies on today’s society. The hypotheses of the article are that there is indeed a connection between the scores obtained by applying DEA method with the ones obtained by the SFA method. Also, it is hypothesized that the level of ICTs use is higher for those countries that are more developed and it is driven by a couple of key factors, chosen as input variables in the present study. The results show that both hypotheses are valid, as the efficiency scores obtained were statistically correlated between the different methods and as the variables chosen as inputs were significant in the SFA model.